Active labour market policies in a recession - Torben M. Andersen; Michael Svarer (IZA Journal of Labor Policy, 2012)
A major labour market challenge following the Great Recession is to avoid an increase in long-term unemployment and thus the structural unemployment rate. Active labour market policies may play an important role in this respect. We consider these issues with outset in Denmark which is a country relying extensively on active labour market policies. It is also characterised by high flows into and out of employment, implying that most unemployment spells are rather short and the unemployment rate is relative low. These features have been maintained despite the crisis, and in this sense the Danish flexicurity model has coped reasonably well with the crisis. The Danish active labour market policies have been continuously changed in light of experience, new knowledge and changes in the labour market situation. This paper reviews and discusses these changes in light of the recession and considers how the labour market has coped with the recession.
Keywords: J60; J38; E32; 330; active labour market policy; long-term unemployment; great recession; Konjunkturelle Arbeitslosigkeit; Arbeitsmarktpolitik; Langzeitarbeitslosigkeit; Dänemark